Great answers to difficult questions about death [ what children need to know - Goldman, Linda , 1946- (Jessica Kingsley Publisher, 2009)
Why do people die?. Where is heaven?. Will I die too? What happens to me?. Death is never an easy subject for discussion and adults can have difficulty finding the right words when talking about it with children. This book explores children's thoughts and feelings on the subject and provides parents and other caring adults with guidance on how to respond to difficult questions. The author covers some of the common questions that children ask about death and provides sensitive yet candid answers in a way that children will be able to understand and relate to. Each chapter is devoted to a partic